Platelet-Targeted FVIII Gene Therapy Restores Hemostasis and Induces Immune Tolerance for Hemophilia A - Cai, Yuanhua; Shi, Qizhen (Frontiers in Immunology, 2020)
Platelets are small anucleated blood components primarily described as playing a fundamental role in hemostasis and thrombosis. Over the last decades, increasing evidence has demonstrated the role of platelets in modulating inflammatory reactions and immune responses. Platelets harbor several specialized organelles: granules, endosomes, lysosomes, and mitochondria that can synthesize proteins with pre-stored mRNAs when needed. While the functions of platelets in the immune response are well-recognized, little is known about the potential role of platelets in immune tolerance. Recent studies demonstrate that platelet-specific FVIII gene therapy can restore hemostasis and induce immune tolerance in hemophilia A mice, even mice with preexisting anti-FVIII immunity. Here, we review the potential mechanisms by which platelet-targeted FVIII gene therapy restores hemostasis in the presence of anti-FVIII inhibitory antibodies and induces immune tolerance in hemophilia A.